Answer:
x=0, y=4 and z=0.
Step-by-step explanation:
Given the system of linear equations:
![\begin{gathered} 3x+2y+z=8 \\ x+y+2z=4 \\ 4x+y+z=y \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/m6ac0792d8y0n3pjb6siy9r8evotoe8osu.png)
From the third equation:
![\begin{gathered} 4x+y-y+z=0 \\ 4x+z=0 \\ z=-4x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/g27b2bkkcls1gx40wbcpdjo7qggmjzcwhe.png)
Substitute z=-4x into the first and second equations.
![\begin{gathered} 3x+2y-4x=8 \\ -x+2y=8 \\ \text{Second Equation} \\ x+y+2z=4 \\ x+y+2(-4x)=4 \\ x+y-8x=4 \\ -7x+y=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/xia8i3n4i6lfsiqe0f24wl9aag4qmuvnhb.png)
Solve the two results simultaneously.
![\begin{gathered} -x+2y=8\implies x=2y-8 \\ -7x+y=4 \\ -7(2y-8)+y=4 \\ -14y+56+y=4 \\ -13y=4-56 \\ -13y=-52 \\ y=-(52)/(-13) \\ y=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/yjozk6bvbox84qlz1oguy5g2wbp88v0t1k.png)
Substitute y=4 to solve for x.
![\begin{gathered} -7x+y=4 \\ -7x+4=4 \\ -7x=4-4 \\ -7x=0 \\ x=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/syhepk60rgwxuibiywbx9mhyj0aq9p52wu.png)
Finally, recall that: z=-4x
![z=-4(0)=0](https://img.qammunity.org/2023/formulas/mathematics/college/co9r1p0809yqxba5evwhqzq21ov9z50yt2.png)
Therefore x=0, y=4 and z=0.